POTRET PEREMPUAN PARANGTRITIS DALAM FILM SITI - Efri Khoirunnisa Hartoyo; Sumekar Tanjung (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2018)
This study aims to explain the representation of Parangtritis women in the Siti movie. Coastal women plays an important role in economic activities on the land. The system of division of labor in coastal communities requires women to be involved in the public sphere. Through the semiotic method of Roland Barthes, this research reveals the repre- sentation of coastal women through the four shots shown. There are three findings in this study. First, coastal women are inseparable from the devotion to the husband and family. Second, helping their husband's income in the public space. Third, self helplessness which resulted in limited area of work in public space. These three findings are not a research effort to generalize the portraits of coastal women. With the dual roles, eventually coastal women cannot escape from their domestic responsibilities due to economic distress.